Indigenous Partnership and Two-Eyed Seeing in Sea Lamprey Management: Lessons Learned from the Denny's Dam Rehabilitation with the Saugeen Ojibway Nation - Nonkes, Charity Grace (Université d'Ottawa / University of Ottawa, 2022)
Bridging knowledge systems is a potential means of equitably and collaboratively working towards shared goals in aquatic ecosystems, such as the management of invasive species. Invasive species pose a significant threat to aquatic ecosystems, and one example of an invasive species with an established control program are sea lamprey (Petromyzon marinus) within the Laurentian Great Lakes. Sea lamprey management faces many challenges including climate change and the apparent declining social acceptance of control programs, especially amongst Indigenous communities in the region. Such challenges illustrate the need for sea lamprey management to better engage Indigenous Nations and knowledge systems. Etuaptmumk (Two-Eyed Seeing) is a Mi’kmaw concept that can facilitate knowledge bridging as it enables Indigenous and Western knowledge systems to work together in parallel on a shared issue. This thesis research uses social science and Indigenous methodologies to understand the Denny’s Dam rehabilitation (sea lamprey barrier) as a case study for relationship-building and knowledge coexistence between Indigenous and non-Indigenous parties in sea lamprey control. Virtual semi-structured interviews (n = 14) were conducted with key decision-makers and others involved in the Denny’s Dam rehabilitation. Results illustrated why and how a knowledge coexistence approach (e.g. Two-Eyed Seeing) could bridge knowledge systems to inform a shared decision-making process. Moreover, findings outline four main factors needed for relationship-building. This study provides practical guidance for practitioners and addresses a gap in the literature concerning Indigenous engagement in sea lamprey management and knowledge coexistence/Two-Eyed Seeing in aquatic invasive species management.
Keywords: sea lamprey; sea lamprey control; sea lamprey management; Two-Eyed Seeing; knowledge coexistence; Indigenous partnership